Carotid endarterectomy for symptomatic carotid stenosis. - Kittipan Rerkasem (2018)
Severe narrowing (stenosis) of the carotid artery is an important cause of stroke. Surgical treatment (carotid endarterectomy) may reduce the risk of stroke, but carries a risk of operative complications. To determine the balance of benefit versus risk of endarterectomy plus best medical management compared with best medical management alone in patients with a recent symptomatic carotid stenosis (i.e. transient ischaemic attack (TIA) or non-disabling stroke). We searched the Cochrane Stroke Group Trials Register (July 2010), MEDLINE (1966 to March 2010), EMBASE (1990 to March 2010) and three other databases, and handsearched relevant journals and reference lists. Randomised controlled trials.   Two review authors independently selected studies and extracted the data. We included three trials. As the trials differed in the methods of measurement of carotid stenosis and in the definition of stroke, we did a pooled analysis of individual patient data on 6092 patients (35,000 patient years of follow-up) after reassessment of the carotid angiograms and outcomes from all three trials using the primary electronic data files and redefined outcome events where necessary to achieve comparability.On re-analysis, there were no statistically significant differences between the trials in the risks of any of the main outcomes in either of the treatment groups or in the effects of surgery. Surgery increased the five-year risk of ipsilateral ischaemic stroke in patients with less than 30% stenosis (N = 1746, absolute risk reduction (ARR) -2.2%, P = 0.05), had no significant effect in patients with 30% to 49% stenosis (N = 1429, ARR 3.2%, P = 0.6), was of marginal benefit in patients with 50% to 69% stenosis (N = 1549, ARR 4.6%, P = 0.04), and was highly beneficial in patients with 70% to 99% stenosis without near-occlusion (N = 1095, ARR 16.0%, P < 0.001). However, there was no evidence of benefit (N = 262, ARR -1.7%, P = 0.9) in patients with near-occlusions.Benefit from surgery was greatest in men, patients aged 75 years or over, and patients randomised within two weeks after their last ischaemic event and fell rapidly with increasing delay. Endarterectomy is of some benefit for 50% to 69% symptomatic stenosis and highly beneficial for 70% to 99% stenosis without near-occlusion. Benefit in patients with carotid near-occlusion is marginal in the short-term and uncertain in the long-term. These results are generalisable only to surgically-fit patients operated on by surgeons with low complication rates (less than 7% risk of stroke and death). Benefit from endarterectomy depends not only on the degree of carotid stenosis, but also on several other factors, including the delay to surgery after the presenting event.